Progress in Colour Studies 2018
DOI: 10.1075/z.217.20mot
|View full text |Cite
|
Sign up to set email alerts
|

Identifying colour use and knowledge in textile design practice

Abstract: A survey of the colour understanding and practice of respondents undertaking a postgraduate programme in textile design is reported. Colour use and knowledge within creative practices was explored, with a view to providing a platform for the field to reflect on assumptions about preference, harmony and colour selectivity in design. Respondents reported on their acquisition of colour mixing knowledge and described their colour palette. Language terms used tended towards basic colour terms and descriptive refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Designers should learn colour science and its application but do not necessarily do so. Mottram found that although design students may be familiar with, and some of them may even be able to describe terms like CMYK, mood board, Pantone, and RGB, they are not familiar with and cannot describe terms like CIE space, Munsell, NCS, and wavelength. Csillag et al found in a recent survey that in the state of São Paulo (Brasil), out of 153 design courses, only 26.8% has explicit colour content.…”
Section: Why Do Nonscientists Need Colour Science?mentioning
confidence: 99%
“…Designers should learn colour science and its application but do not necessarily do so. Mottram found that although design students may be familiar with, and some of them may even be able to describe terms like CMYK, mood board, Pantone, and RGB, they are not familiar with and cannot describe terms like CIE space, Munsell, NCS, and wavelength. Csillag et al found in a recent survey that in the state of São Paulo (Brasil), out of 153 design courses, only 26.8% has explicit colour content.…”
Section: Why Do Nonscientists Need Colour Science?mentioning
confidence: 99%